Pemahaman Misi Lintas Budaya Melalui “Kursus Kairos” Bagi Kaum Awam Di Persekutuan Doa Kasih Ilahi Malang - Chen Siauw Siauw (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2023)
Cross-cultural mission services, especially for the laity, in this case, non-theological students and activists have not been fully understood properly and correctly. The Kairos course will equip participants with a new understanding and paradigm of Biblical cross-cultural missions, especially for neglected tribes. Providing the right understanding so that they are able to recognize their calling correctly to be able to take part in cross-cultural missionary service. Through the Kairos course it is hoped that the participants will actively participate with God's servants and the Congregational Pastor in outreach services for neglected tribes, be able to provide the right understanding and direction about cross-cultural missions, so that the mission program becomes effective in mobilizing the congregation to be actively involved. Lay people are able to become partners and co-workers of God's servants and assemblies or elders, especially in empowering evangelistic ministries with a wider but specific reach. The method used to provide an understanding of cross-cultural missions is through the Kairos Course activities which are carried out for five consecutive days in integrated material sessions.